2012
DOI: 10.2202/1544-6115.1713
|View full text |Cite
|
Sign up to set email alerts
|

A Family-Based Probabilistic Method for Capturing De Novo Mutations from High-Throughput Short-Read Sequencing Data

Abstract: Recent advances in high-throughput DNA sequencing technologies and associated statistical analyses have enabled in-depth analysis of whole-genome sequences. As this technology is applied to a growing number of individual human genomes, entire families are now being sequenced. Information contained within the pedigree of a sequenced family can be leveraged when inferring the donors' genotypes. The presence of a de novo mutation within the pedigree is indicated by a violation of Mendelian inheritance laws. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…An entire class of computational tools has arisen that utilize both sequencing data and pedigree information to identify de novo mutations genome wide. Most of these tools currently deal with trios (mother, father, and child) only and can identify de novo variants arising in the children (Cartwright et al, 2012; http://sourceforge.net/p/denovogear/wiki/Home/; Li et al, 2012; Li, 2011). Because sequencing reads have a higher error rate than traditional genotyping, these tools incorporate information about coverage, the sequencing error rate, the expected de novo mutation rate, and family relationships.…”
Section: Genomic Analysismentioning
confidence: 99%
“…An entire class of computational tools has arisen that utilize both sequencing data and pedigree information to identify de novo mutations genome wide. Most of these tools currently deal with trios (mother, father, and child) only and can identify de novo variants arising in the children (Cartwright et al, 2012; http://sourceforge.net/p/denovogear/wiki/Home/; Li et al, 2012; Li, 2011). Because sequencing reads have a higher error rate than traditional genotyping, these tools incorporate information about coverage, the sequencing error rate, the expected de novo mutation rate, and family relationships.…”
Section: Genomic Analysismentioning
confidence: 99%
“…In the ALL quartet, SNP calling from exome data was performed as described in Supplemental Methods. De novo mutation discovery was performed using the DND software (Cartwright et al 2012). In the 22 trios, we called SNPs in parents using Samtools and only SNPs within targeted regions with Phred score above 30 were kept.…”
Section: Exome Sequencing In the Fcall Cohortmentioning
confidence: 99%
“…While we and others have shown that it is feasible to accurately detect de novo point mutations from whole genome sequencing (WGS) data, our ability to reliably detect de novo indels is much less certain 14 . In the recently published Phase I analyses of the 1000 genomes project, experimental validation of an initial indel call set yielded an estimated false discovery rate of 35% 5 .…”
mentioning
confidence: 99%